P-735 Exploring representation and inclusivity in fertility and reproductive health societies' leadership. (30th June 2022) - Usman, N; Grace, B
Abstract: Study question: How diverse is the board-level executive leadership of the leading fertility and reproductive health societies in Europe, Australia and North America? Summary answer: There is good gender diversity among the reproductive health societies included in the study, with limited ethnic diversity. What is known already: Reproductive health societies promote understanding and interest in reproductive biology and medicine. They are leading authorities, providing guidelines, opinions, and direction to practitioners, policy makers and the public. Membership on these societies' board is a marker of influence and prestige. Many societies have clear Equality and Diversity Statement on their website, suggesting that they value representation of members from whom they obtain fees. This study presents a quantification of the executive leadership demographic diversity of major fertility and reproductive health societies in Europe, Australia and North America to evaluate diversity in governance. Study design, size, duration: We conducted a review of the websites of ten leading fertility and reproductive health societies in the Europe, Australia and North America to quantity gender and ethnic diversity. Data analysis was conducted on the information obtained in January 2022. We included the executive leadership team /governing board members but excluded subgroup leaders or special interest group coordinators. Participants/materials, setting, methods: Organisations reviewed include: American College of Obstetricians and Gynaecologists(ACOG), American Society for Reproductive Medicine(ASRM), British Fertility Society(BFS), Canadian Fertility and Andrology Society(CFAS), European Society of Human Reproduction and Embryology(ESHRE), The Fertility Society of Australia and New Zealand(FSA), International Federation of Obstetrics and Gynaecology(FIGO), The Royal Australian and New Zealand College of Obstetricians and Gynaecologists(RANZCOG), Royal College of Obstetricians and Gynaecologists (RCOG), and The Society of Obstetricians and Gynaecologists of Canada(SOGC). Main results and the role of chance: Proportion for each demographic group at the time of the study are summarised below; where n = total number of board members; Gender: W= women, M= Men; ethnicity: Wh = White, B = Black and A = Asian. ACOG: n = 5; W = 60%, M = 40%; Wh = 60%, B = 0%, A = 40% ASRM: n = 17; W = 59%, M = 41%; Wh = 71%, B = 12%, A = 18% BFS: n = 4; W = 50%, M = 50%; Wh = 75%, B = 0%, A = 25% CFAS: n = 10; W = 50%, M = 50%; Wh = 70%, B = 0%, A = 30% ESHRE: n = 14; W = 57%, M = 43%; Wh = 100%, B = 0%, A = 0% FIGO: n = 10; W = 60%, M = 40%; Wh = 60%, B = 10%, A = 30% FSA: n = 15; W = 60%, M = 40%; Wh = 87%, B = 0%, A = 13% RANZCOG: n = 9; W = 56%, M = 44%; Wh = 78%, B = 0%, A = 22% RCOG: n = 6; W = 50%, M = 50%; Wh = 83%, B = 0%, A = 17% SOGC: n = 22; W = 68%, M = 32%; Wh = 100%, B = 0%, A = 0% In total, the number of board level/executive leadership members, responsible for governance in the societies reviewed were 112. Gender diversity was 41% Men, 59% Women, while ethnic diversity was 82% White, 3% Black and 15% Asian. It is encouraging to see the gender parity in the executive leadership of the organisations review, there remains an important need to improve ethnic diversity in order to better represent the membership and wider community  they serve. This has implications for role-modelling, equity, minimising the negative impact of groupthink and reaching/giving underrepresented group a voice. Limitations, reasons for caution: Results presented are based on a snapshot at the time of review. Organisations periodically change leadership. Additionally, gender identification is based on self-identification in individual's profile biography. Wider implications of the findings: As reproductive health organisations continue make extensive contributions to the field, it is important for their leadership to represent the diversity of members and wider population they serve. There remains a need to move beyond diversity and equality statement to actively deploy policies and processes to improve and monitor representation. Trial registration number: not applicable